Performance of latent heat storage (LHS) systems using pure paraffin wax as working substance. (November 2022) - Gunjo, Dawit Gudeta; Yadav, Vinod Kumar; Sinha, Devendra Kumar; Refaey, H.A.; Sayeed Ahmed, Gulam Mohammed; Abelmohimen, Mostafa A.H.
Abstract: No single energy source, either conventional, or renewable, is self-sufficient to meet the energy demand of any country. The intermittency in the supply of energy, as in the case of solar radiation, creates a mismatch between the demand and the supply of the energy. This necessitates the development of an efficient energy storage system that can be used as stand-by in case of unavailability of the primary energy source. A properly designed thermal storage system may overcome inherent intermittency of energy supply. In the present work, the charge-discharge characteristics of the 5 MJ capacity storage system, based on latent heat storage, with paraffin wax as a phase change substance, is numerically investigated. The performance of shell and tube type device is evaluated using COMSOL®4.3a software. The results revealed that the paraffin wax, as a Phase Change Material (PCM), charges more quickly (25% faster) as compared to discharge. The PCM with a latent heat of 168 kJ/kg, was found suitable for effective heat storage and does not undergo sub-cooling. This work suggests that the selection of the heat exchangers, based on charging time, may be done by suitably designing the number of tubes. In this work, the tubes in the heat exchanger were varied from 9 to 25 and through computational analysis, 17 tubes were found to be the most economical selection with better effectiveness.